Removal of Trace Arsenic to Meet Drinking Water Standards Using Iron Oxide Coated Multiwall Carbon Nanotubes - Ntim, Susana Addo (2011)
This study presents the removal of trace level arsenic to meet drinking water standards using an iron oxide-multi-walled carbon nanotube (Fe-MWCNT) hybrid as a sorbent. The synthesis was facilitated by the high degree of nanotube functionalization using a microwave assisted process, and a controlled assembly of iron oxide was possible where the MWCNT served as an effective support for the oxide. In the final product, 11 % of the carbon atoms were attached to Fe. The Fe-MWCNT was effective in arsenic removal to below the drinking water standard levels of 10 µg L(−1). The absorption capacity of the composite was 1723 µg g(−1) and 189 µg g(−1) for As(III) and As(V) respectively. The adsorption of As(V) on Fe-MWCNT was faster than that of As(III). The pseudo-second order rate equation was found to effectively describe the kinetics of arsenic adsorption. The adsorption isotherms for As(III) and As(V) fitted both the Langmuir and Freundlich models.